Determinants of corporate leverage: evidence from Malaysian service sector - Amirul Azim, Abdul Hamid (2020)
This study investigates the determinants of corporate’s leverage in the non-financial service companies as the debt financing becomes an important source of capital nowadays. The main purpose of this thesis is to identify and analyze the relationship between companyspecific factors and company’s leverage of public listed service companies in Bursa Malaysia. This research paper covers 231 service sector companies from the year of 2008 to 2018 (11 years) on panel data basis. This research paper applies Dynamic panel regression and System-Generalized Method of Moment (S-GMM) since the result indicate this study is genuinely dynamic. The findings of this study show that company-specific variables such as size (SIZETAi,t), profitability (PROROEi,t), liquidity (LIQRi,t), prior leverage (LagLEVi,t-1) and growth opportunities (GROPi,t) are significantly influence company’s leverage (LEVi,t ). However, variables such as sustainability (SUSAgei,t), profitability (PRONPMi,t) and liquidity (LICashRi,t) are insignificant on company’s leverage. Furthermore, results also indicate SUSAgei,t, PROROEi,t and LIQRi,t support Pecking Order Theory (POT) while the rest (SIZETAi,t, LagLEVi,t-1, GROPi,t, PRONPMi,t and LICashRi,t) support Trade-off Theory (TOT).